The In Vitro Differentiation of Human CD141+CLEC9A+ Dendritic Cells from Mobilized Peripheral Blood CD34+ Hematopoietic Stem Cells. Issue 4 (18th April 2022) - Swartz, Adam M.; Nair, Smita K.
Abstract: As shown in various preclinical studies, conventional type‐1 dendritic cells, or cDC1s, play a critical role in the immunological rejection of tumors and in the defense against pathogens. This indispensability stems from their potent capacity to activate cytotoxic T cells, especially via the cross‐presentation of exogenous antigens. For this reason, cDC1s have become an attractive target for immunotherapy. Here we report a simplified method for generating large numbers of cDC1‐like cells in vitro from mobilized human peripheral blood CD34+ hematopoietic stem cells using FMS‐like tyrosine kinase 3 ligand (FLT3L) and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF). An important aspect of this Protocol is the growth of cells on a non‐tissue culture‐treated surface rather than on a tissue culture‐treated surface since the latter suppresses cDC1‐marker expression. The resulting CD11c+ DCs express high levels of cDC1‐specific markers such as CD141, CLEC9A, TLR3, and several DC maturation markers. Compared to alternative differentiation methods, this method generates large numbers of cDC1‐like cells without the need for immortalized feeder cells and should prove useful for studying cDC1 immunobiology and clinical applications of this DC subset. © 2022 Wiley Periodicals LLC. Basic Protocol : Generation of human CD141+CLEC9A+ dendritic cells from mobilized peripheral blood CD34+ hematopoietic stem cells Support Protocol : Flow cytometric immunophenotyping of CD141+ dendritic cells